Can Lutheran Theology and Virtue Ethics Be Friends?. Issue 1 (March 2017) - Hoffmeyer, John F.
Abstract: Lutheran theology is generally suspicious of virtue ethics. This suspicion arises from (1) the Lutheran commitment to justification by faith in God's unconditional promise; and (2) Luther's corollary understanding of sin as existential self‐absorption. Some Lutheran theologians have sought to incorporate virtue ethics by using it as an orientation for Christian life, while making sure to avoid any contamination of the doctrine of justification by virtue ethics. My project is to consider the possibility of a mutual illumination and interaction between the doctrine of justification and virtue ethics' focus on formation by habituation. As an aid in exploring this possibility I use the distinction in Dietrich Bonhoeffer's Ethics between the "ultimate" and the "penultimate."